In situ evaluation of the remineralizing capacity of pit and fissure sealants containing amorphous calcium phosphate and/or fluoride - Silva, Kelio Garcia [UNESP]; Pedrini, Denise [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Ferreira, Lilian [UNESP]; Cannon, Mark (Taylor & Francis As, 2010)
Objective. This in situ study evaluated the remineralizing potential of pit and fissure sealants containing amorphous calcium phosphate (ACP) and/or fluoride in artificially induced carious lesions on smooth enamel surfaces. Material and methods. Ten volunteers who wore acrylic palatal devices were enrolled in this 5-day double-blind study and assigned to one of the following five groups: (I) demineralized enamel slab+Fluroshield (sealant with fluoride); (11) demineralized enamel slab+Aegis (sealant with ACP); (III) demineralized enamel slab+experimental sealant with fluoride (ESF); (IV) demineralized enamel slab +experimental sealant with fluoride/ACP (ACP-F); and (V) demineralized enamel slab (control). After the experimental period, the percentage of surface microhardness recovery(%SMHR) and the integrated loss of subsurface hardness (Delta KHN) were evaluated. The concentrations of fluoride, calcium and phosphorus in enamel were also determined. Results. The sealants containing ACP and/or fluoride presented a higher remineralizing capacity (%SMHR and Delta KHN) than that of the control group. Aegis provided either more efficient or similar remineralization than the other sealants. The association between ACP and fluoride did not show a greater efficacy in the remineralization. F, Ca and P concentrations in enamel varied according to the group. Conclusion. The pit and fissure sealants containing ACP were able to promote remineralization of artificially induced carious lesions on smooth enamel surfaces.
Keywords: Calcium phosphates; fluorides; pit and fissure sealants; tooth remineralization